1980
DOI: 10.1007/bf00016247
|View full text |Cite
|
Sign up to set email alerts
|

Massive cultivation of microalgae: Results and prospects

Abstract: An account is given of the development of the utilization of microalgae for food and feed with special emphasis on the advantages of algal technologies for tropical and subtropical countries. The present status of microalgae mass production is characterized with respect to technology, product properties, yields, nutrition, toxicology and economics. As a multipurpose operation, the treatment of liquid wastes with algae-bacteria systems is the most promising microalgal technology. It yields proteinaceous microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(33 citation statements)
references
References 19 publications
0
32
0
1
Order By: Relevance
“…The concept of areal biomass density was first suggested by Soeder (1980) as an important factor in determining productivity in algal mass cultures. It was suggested that cultures should be operated at an areal mass density ranging between 50 and 150 g m-2.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of areal biomass density was first suggested by Soeder (1980) as an important factor in determining productivity in algal mass cultures. It was suggested that cultures should be operated at an areal mass density ranging between 50 and 150 g m-2.…”
Section: Discussionmentioning
confidence: 99%
“…Soeder (1980) suggested that cultures should be operated at areal densities of between 50 to 150 g (d. wt) m -2 . Using a mathematical model that predicts algal productivity from input variables of light energy, temperature and biomass concentration, Grobbelaar (1981aGrobbelaar ( , 1982 and Grobbelaar et al (1984Grobbelaar et al ( , 1990 determined the optimal areal density for green microalgae, grown under average conditions in outdoor mass algal cultures, to be about 40 to 45 g (d.wt) m -2 .…”
Section: Introductionmentioning
confidence: 99%
“…The requirement of high nitrogen content and the other related chemical fertilizers to cultivate microalgae on a large scale has moved the process towards a loss of the environment. Also, cultivation of microalgae can basically play an important role as a self-purification process of the wastewaters in a natural condition (Soeder 1980). Municipal wastewater using conventional treatment that involves primary and secondary bio-treatment helped to remove only a portion of the nitrogen and phosphorus contained in the wastewater (Orpez et al 2009).…”
Section: Integrated Palm Oil Mill Effluent Treatment and Biofuel Prodmentioning
confidence: 99%